2007
DOI: 10.1017/s1431927607072972
|View full text |Cite
|
Sign up to set email alerts
|

FIB Characterization of the Cathode Microstructure in a Single Solid Oxide Fuel Cell (SOFC)

Abstract: The relationship between the cathode microstructure and electrochemical performance of lanthanum strontium manganite (LSM) /yttria stabilized zirconia (YSZ) SOFCs was studied for the isochronal sintering at temperatures between 950°C and 1400°C for 1 hour. Previous studies have shown that the Triple-Phase-Boundary (TPB) length at the cathode/electrolyte interface contributes to charge transfer resistance. However, it is unclear the role of the tertiary phase formation. This study investigated the effects of 1)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…Several studies have indicated that La 2 Zr 2 O 7 forms for x !0.0 and SrZrO 3 along with the La 2 Zr 2 O 7 starts to form for x !0.3 [6,24,26], while other studies reported that both zirconates can form at x !0.17, which is also consistent with thermodynamic calculations [19,23]. Formation of SrZrO 3 at 1:1 LSM and YSZ ratio and La 2 Zr 2 O 7 at 1:3 ratio was reported during annealing at 1000 C in N 2 (PO 2 w 10 À5 atm) atmosphere [27]. However, SrZrO 3 formation was not observed when LSM and YSZ ratio !1.0 [19].…”
Section: Introductionsupporting
confidence: 88%
See 2 more Smart Citations
“…Several studies have indicated that La 2 Zr 2 O 7 forms for x !0.0 and SrZrO 3 along with the La 2 Zr 2 O 7 starts to form for x !0.3 [6,24,26], while other studies reported that both zirconates can form at x !0.17, which is also consistent with thermodynamic calculations [19,23]. Formation of SrZrO 3 at 1:1 LSM and YSZ ratio and La 2 Zr 2 O 7 at 1:3 ratio was reported during annealing at 1000 C in N 2 (PO 2 w 10 À5 atm) atmosphere [27]. However, SrZrO 3 formation was not observed when LSM and YSZ ratio !1.0 [19].…”
Section: Introductionsupporting
confidence: 88%
“…Mn ions diffuse readily in YSZ due to its smaller ionic radii and the highest diffusivity among the constituent lanthanum and strontium ions [6,27]. The Mn in solid solution is a mixture of Mn 3þ and Mn 2þ [45].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown previously that the 3D architecture of electrodes in electrochemical energy devices can be investigated in detail by the focused ion beam (FIB)-scanning electron microscopy (SEM) slice&view technique and subsequent 3D reconstruction. [12,13,14,15] This technique has for instance been used to study degradation phenomena in PEM fuel cell electrodes, [16,17] as well as the impact of various electrode fabrication processes on the resulting 3D electrode structure. [18] Early work by Ettingshausen et al [19] and Litster et al [2] already indicated the important role of the support material's shape for the formation of the porous structure of the catalytic layer in fuel cells.…”
Section: Introductionmentioning
confidence: 99%